Teaching reading skill promotes effective learning of future tense among the first-year undergraduates of faculty of management and commerce and ramanathan academy of fine arts at the university of jaffna. - Patrick, J.J.D. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
The aim of this study is to find out whether teaching reading skill promotes effective learning of future tense of English as a Second Language (ESL) among the first-year students of Faculty of Management studies and Commerce and the Ramanathan Academy of Fine Arts (Faculty of Arts). The research problem is that “how far teaching reading skill helps to improve learning of future tense. In order to find out the solution to the research problem, mixed method research methodology was employed. In the quantitative study, experimental method in the form of pre, post-test was adopted and probability sampling was used to select the subjects. A specially devised pretest based on four types of future tense was administered for the experimental group and the control group. A similar test was administered as posttest for these two groups. However, for the experimental group a similar third reading activity with explanation of teacher was devised, and this treatment was not given to the control group. The quantitative results weretriangulated by using participant observation. In the post test, participants who performed inadequately in the pretest (before intervention of reading), scored well in both experimental group and control group. Hence, theresults of posttest revealed that participants in the experimental group scored higher than they scored in the pretest.
Keywords: Reading Test; Future Tense; Experimental Method; Participant Observation; Mixed Method